Tiktok Lexical Contents in Use: Attitudes among Bachelor of Arts in English Language (ABEL) Students - Francis Ian M. Guillermo; Richard Sambajon Agbayani (Randwick International of Education and Linguistics Science Journal, 2024)
The rise of TikTok as an educational tool has opened new avenues for vocabulary development among its users. This study explored the vocabulary levels and attitudes of 90 first- and second-year AB English Language (ABEL) students towards TikTok videos containing vocabulary content. Participants engaged voluntarily in a mixed-method research design, incorporating pretests and posttests, treatment, and interviews. Quantitative data were analyzed using T-tests, frequency, and percentage, while qualitative data underwent thematic analysis to uncover participants' cognitive, affective, and behavioral attitudes. The findings revealed a notable improvement in the participants' vocabulary knowledge, as demonstrated by higher posttest scores following the use of TikTok videos. Despite some challenges with the application, participants generally held positive attitudes towards the treatment, recognizing its contribution to their vocabulary enhancement. The study suggests that both English teachers and students could effectively use TikTok videos with lexical content for vocabulary teaching and learning. Additionally, the study highlights the potential for future research to investigate the role of TikTok videos in aiding non-English speakers with foreign language acquisition and other language skills, as this study focused solely on vocabulary development among English language majors.